Operation of wastewater treatment plant under nitrogen overload conditions from fermentation effluents - Pęciak-Foryś, Grażyna; Barbusiński, Krzysztof; Żołnierczyk, Maciej (Instal, 2021)
In recent years, both in large and smaller urban agglomerations, both for economic reasons and due to economy industrial transformations, water consumption is significantly smaller than was originally assumed in estimates and design specifications for wastewater treatment plants. At the same time, the development of innovative environmental technologies has allowed the modification of selected technological units in wastewater treatment plants, especially in the field of nitrogen removal. The optimization of energy-consuming nitrification/denitrification and the application of new generation processes using shortened nitrogen transformation pathways in side-stream process lines are new directions and strategies for the reduction of nitrogen concentrations in wastewater treatment plants. The publication describes the influence of an additional load of nitrogen returned to the main technological line with effluents from the dewatering of fermented sludge on the technological process in the wastewater treatment plant “Śródmieście” in Zabrze city. It is briefly shown which problems it causes and what countermeasures are and can be applied to maintain the quality parameters of treated wastewater.